(untitled) - Marx, Cheryle E. (Amsterdam ( The Netherlands ), 1991)
This dictionary contains terms related to the various types of aquaculture practiced in the world today. It covers hatchery, nursery, and growout production for fish culture, crustacean and mollusc culture, algal culture, reptile culture, amphibian culture, and echinoderm culture. There are terms for pathology, prophylaxis, breeding, nutrition, genetics, hydrology, engineering, marketing, biology, systems behavior, chemicals, and water chemistry. The names of species cultured and past species are also included with the appropriate Latin names. Most of the disease names have a short description in parentheses that names the pathogen and the type of animals that are prone to the disease, to avoid confusion with other diseases that have similar names.
Keywords: Aquaculture; Dictionaries